2021
DOI: 10.24843/eja.2021.v31.i10.p13
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model UTAUT 2 untuk Menjelaskan Minat dan Perilaku Penggunaan Mobile Banking

Abstract: The purpose of this study was to determine the factors that influence the interest and behavior of using mobile banking by applying the UTAUT2 model. The variables used in this study are performance expectations, business expectations, socio-cultural factors, facilitating conditions, hedonic motivation, price values and habits. This research was conducted in Badung Regency. Determination of the sample is done by accidental sampling technique. Data was collected by distributing online questionnaires. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0
24

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 8 publications
4
3
0
24
Order By: Relevance
“…As evidenced by the increasing number of encouragement from the surrounding environment, it will be easy for someone to influence the decision to take action from the surrounding environment. The results of this study support previous research conducted by (Andini & Hariyanti, 2021) and (Nopiani & Putra, 2021) which showed hedonic motivation had a positive and significant effect on interest in using the software. So, it is concluded that H4 is accepted.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As evidenced by the increasing number of encouragement from the surrounding environment, it will be easy for someone to influence the decision to take action from the surrounding environment. The results of this study support previous research conducted by (Andini & Hariyanti, 2021) and (Nopiani & Putra, 2021) which showed hedonic motivation had a positive and significant effect on interest in using the software. So, it is concluded that H4 is accepted.…”
Section: Resultssupporting
confidence: 90%
“…The role of the people around the individual in providing opinions or recommendations is the main driver for individuals using technology (Wardhana, 2019). Also supported by research (Nopiani & Putra, 2021). Based on the explanation above, it can be hypothesized as follows: H4: Social influence has an influence on interest in using accounting software.…”
Section: Effect Of Social Influence On Interest In Using Accounting S...mentioning
confidence: 91%
“…Berdasarkan penelitian terdahulu tentang perilaku minat telah dilakukan pada industri makanan organik (Hughner, McDonagh, Prothero, Shultz, & Stanton, 2007), perbankan (Pertiwi & Ariyanto, 2017), media sosial (Heinonen, 2011), transportasi (Ningsi & Putriyani, 2019), mobile payment (Liu, Lou, & Zhang, 2020).…”
Section: Pendahuluan Latar Belakangunclassified
“…Dalam penelitian ini, ekspektasi kinerja pada minat penggunaan layanan mobile banking dapat dirasakan oleh pengguna dengan adanya berbagai manfaat yang ditawarkan untuk melakukan berbagai teransaksi secara online. Hasil penelitian yang dilakukan oleh Pertiwi & Ariyanto (2017) serta Mufingatun et al, (2020) menyatakan bahwa ekspektasi kinerja berpengaruh positif dan signifikan terhadap minat penggunaan mobile banking. Namun hasil penelitian Oktafani & Sisilia (2020) menyatakan ekspektasi kinerja tidak memiliki pengaruh terhadap minat penggunaan dompet digital OVO.…”
Section: Pendahuluanunclassified